2013
DOI: 10.1002/art.38180
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Ubiquitin Proteasome Pathway in a Mouse Model of Inflammatory Myopathy: A Potential Therapeutic Target

Abstract: Objective Myositis is characterized by severe muscle weakness. We and others have previously shown that endoplasmic reticulum (ER) stress plays a role in the pathogenesis of myositis. The present study was undertaken to identify perturbed pathways and assess their contribution to muscle disease in a mouse myositis model. Methods Stable isotope labeling with amino acids in cell culture (SILAC) was used to identify alterations in the skeletal muscle proteome of myositic mice in vivo. Differentially altered pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
(68 reference statements)
1
23
0
1
Order By: Relevance
“…129 Upregulation of the expression of MHC class I molecules in skeletal muscle fibers is an early feature of IIM and ectopic expression of the molecule induced ER stress response and resulted in a disease that shares several features with human IIM. 130,131 Considering that muscle injury and the associated inflammatory response represent rather common event in vivo, 109 the relative rarity of IIM indicates that a number of events must simultaneously occur to set the stage for self-sustaining autoimmunity. We have recently observed that apoptotic myoblasts are immunogenic only if appropriate adjuvants are provided in the injured/regenerating muscle.…”
Section: Figurementioning
confidence: 99%
“…129 Upregulation of the expression of MHC class I molecules in skeletal muscle fibers is an early feature of IIM and ectopic expression of the molecule induced ER stress response and resulted in a disease that shares several features with human IIM. 130,131 Considering that muscle injury and the associated inflammatory response represent rather common event in vivo, 109 the relative rarity of IIM indicates that a number of events must simultaneously occur to set the stage for self-sustaining autoimmunity. We have recently observed that apoptotic myoblasts are immunogenic only if appropriate adjuvants are provided in the injured/regenerating muscle.…”
Section: Figurementioning
confidence: 99%
“…BTZ prolongs survival during lethal hemorrhagic shock in rats [11]. Rayavarapu et al showed that BTZ significantly improved muscle function and reduced tumor necrosis factor α expression in the skeletal muscle of mice with myositis [12]. Furthermore, the potential use of BTZ in treating cancer cachexia has also been attempted [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to making the cells vulnerable to cytotoxic T cell injury, overexpression of HLA class I antigens leads to protein accumulation and misfolding in the endoplasmic reticulum (ER). Such misfolding activates the ER stress pathway leading to activation of the NFκB pathway with enhanced synthesis of pro‐inflammatory cytokines and endogenous class I MHC up‐regulation, and ER death pathway through caspase 12, leading to muscle degeneration . In presence of necrotic cell materials, muscle autoantigens released from regenerating muscles may activate IFN .…”
Section: Regenerating Muscle Cellsmentioning
confidence: 99%
“…Inhibition of the ubiquitin proteasome pathway with bortezomib improved muscle function in a mouse model of myositis …”
Section: Emerging Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation